Partial androgen insensitivity syndrome presenting as pubertal gynecomastia: clinical and hormonal findings and a novel mutation in the androgen receptor gene. (28th December 2018) - Vaidyanathan, Priya; Kaplowitz, Paul
Summary: Pubertal gynecomastia is common, can be seen in 65% of the adolescent boys and is considered physiological. It is thought to be due to transient imbalance between the ratio of testosterone and estradiol in the early stages of puberty. It resolves in 1–2 years and requires no treatment. However, more persistent and severe pubertal gynecomastia is less common and can be associated with pathological disorders. These can be due to diminished androgen production, increased estrogen production or androgen resistance. We report a case of persistent pubertal gynecomastia due to partial androgen insensitivity syndrome (PAIS), classical hormone findings and a novel mutation in the androgen receptor (AR) gene. Learning points: Laboratory testing of follicle-stimulating hormone (FSH), leutinizing hormone (LH) and testosterone for pubertal gynecomastia is most helpful in the setting of undervirization. The hormonal finding of very high testosterone, elevated LH and estradiol and relatively normal FSH are classical findings of PAIS. Gynecomastia due to PAIS will not resolve and surgery for breast reduction should be recommended.